Analisis Nilai Tambah Agroindustri Gula Aren (Studi Kasus Pada CV. Putri Tunggal) di Desa Salupangkang Kecamatan Topoyo Kabupaten Mamuju Tengah - Santi Susilawati (Universitas Merdeka Madiun, 2022)
This study aims to: 1). This study aims to determine the process of processing palm sap into palm sugar in Salupangkang Village, Topoyo District, Central Mamuju Regency. 2). To find out the added value of palm sugar agroindustry in Salupangkang Village, Topoyo District, Central Mamuju Regency. This palm sugar agroindustry is one of the businesses that has developed in Salupangkang Village, Topoyo District, Central Mamuju Regency. This industry is expected to improve product quality, profitability, and added value. The object of this research is focused on the CV. Putri Tunggal. The informant determination technique was used to answer and provide information to researchers. The data collected includes primary data and secondary data. Data analysis was carried out using the value-added analysis format according to the method of Hayami et al. The results showed that the added value obtained in the palm sugar agroindustry was Rp. 792/Kg of raw materials with a ratio of Rp. 26.4%, Profit from palm sugar agroindustry is Rp. 786.25, with a profit rate of 26.20%. The added value produced means that the palm sugar agroindustry has succeeded in transforming palm juice into palm sugar products so that it has more value than palm juice itself.